Profit optimisation in three echelon supply chain revenue management through new heuristic optimiser. (12th February 2009) - Kadadevaramath, R.S.; Prasad, P.S.S.; Mohanasundaram, K.M.; Immanuel, E.A.; , K. Rameshkumar
In recent years, many of the developments in supply chain revenue management are connected to the need of information of efficient supply chain flow; modelling and optimisation, are most important in order to maximise the profit of supply chain because the cost of material, manufacturing and distribution and inventory accounts for 70-80% value of the product. Hence, tactical supply chain design has become a major challenge for firms so as to improve the revenue of the organisation. Particle swarm optimisation is used to optimise the supply chain operations with the objective of maximising the profit of the supply chain revenue.